BRS FC415: common bean cultivar with high yield, commercial quality, slow seed coat darkening, and resistance to soil pathogens. - PEREIRA, H. S. (2022)
BRS FC415 is a common bean cultivar with carioca grain type, high commercial quality, and slow seed coat darkening. It has wide adaptation to different production regions, high mean yield (2,310 kg ha-1), high yield potential (3,901 kg ha-1), and resistance to Fusarium wilt, root rots, and anthracnose.